ALOKASI PENDAPATAN DAN LITERASI KEUANGAN Studi Kasus pada Desa Sidomukti Kecamatan Plaosan Kabupaten Magetan - Nurul Hidayah (Universitas Pamulang, 2018)
AbstractThis study aims to determine the allocation of income and financial understanding to working housewives and housewives who do not work in the Village Sidomukti Plaosan District Magetan. This study used a survey method conducted to 80 respondents consisting of 40 housewives who do not work and 40 housewives who work. This research uses descriptive and explanative research method. This research is done by collecting data to describe and give more detailed explanation about phenomenon of research subject then explain the relationship between phenomena. The results of this study illustrate that there is no significant difference between housewives who do not work and work in the allocation of income. While the level of financial literacy with high categories more owned by working housewives. In addition, the relationship between the level of financial literacy with the allocation of income between both types of housewives has opposite results. Housewives who do not work with high levels of financial literacy are more efficient in allocating their income while for working mothers get the opposite. Keywords: Housewife, income allocation, financial literacy